Scrutinizing the Criteria for Character Strengths: Laypersons Assert That Every Strength Is Positively Morally Valued, Even in the Absence of Tangible Outcomes - Stahlmann, Alexander G.; Ruch, Willibald (Frontiers in Psychology, 2020)
This study examines Peterson and Seligman’s (2004, p. 19) claim that every VIA character strength “(…) is morally valued in its own right, even in the absence of obvious beneficial outcomes”. Although this criterion assumes a pivotal role in distinguishing character from personality, no previous study has investigated its validity. Based on what Peterson and Seligman (2004) have provided us with, we describe how we built our study around indirectly testing every strength’s assumed moral evaluation, in which inclinations toward deontology (e.g., “torture is wrong regardless of tangible positive outcomes”) and consequentialism (e.g., “torture can be good if it accounts for more positive than negative outcomes”) may play a critical role. We used Peterson and Seligman’s (2004) handbook to construct four ultra-short stories for every strength: The stories depict various agents engaging in strength-related behavior (e.g., a young student courageously stepping up against school bullies). We prompted participants to rate these and twelve anchor stories multiple times as to whether the agents acted morally correct: In the first block, the actions’ consequences were undetermined while in the second block, the actions had either positive, negative, or mixed consequences, which we used to compute proxies of participants’ inclinations toward deontology and consequentialism. The ratings of N = 230 German-speaking laypersons suggest that the criterion stands: Participants perceived every strength as positively morally valued when consequences were undetermined, and positive consequences did not account for or increase this effect. However, moral value seems to come in degrees, and some strengths were valued more strongly than others (top five: judgment, honesty, kindness, fairness, and hope). Furthermore, specific character strengths (measured by self-report) were connected with more positive evaluations (e.g., endorsing spirituality was connected with rating spirituality as more positively valued). Both deontology and consequentialism were connected with more positive evaluations, and we suggest two hypotheses to explain how such inclinations can lead to perceiving character strengths as positively valued. Our findings highlight the importance of scrutinizing the criteria for character strengths, and our experimental paradigm can offer a template to further investigate character strengths’ moral evaluation and other fundamental assumptions in upcoming studies.